"Our Artistic Home": Adolescent Girls and Domestic Interiors in the Girl's Own Paper. (4th May 2018) - Yan, Shu-Chuan
Abstract: By zooming in on the Girl's Own Paper ( GOP ), this essay demonstrates how the production and dissemination of shared domestic cultures are directed at adolescent girls through esthetic practices of furnishing and decorating the home. The essay aims to contextualize the role of household art in the relationship between female adolescence and bourgeois domestic interiors in fin de siècle Britain. The relationship reveals three important aspects of domestic cultures: household art, do-it-yourself crafts, and material collecting. First, the GOP advises adolescent girls to read and interpret the language of household art through selection and placing, which, in turn, facilitates the construction of the textuality of interior furnishings. The GOP 's esthetic theory, an integral part of educating and improving girls' taste, functions to enhance their room-layout skills and also construct their architectural identities. Second, adolescent girls are credited with the active role of young home-makers in the GOP . The practice of amateur upholstery shapes female youth's artistic self-expression and manifests their autonomous control over the making of home-crafted objects. And thirdly, the act of collecting furniture pieces and decorative items functions to address the various components of a room alongside contemporary social concerns about good taste. The accumulation of artifacts allows girls to achieve a sense of materiality and ownership contained within the domestic sphere. Home decoration in general provides a focal point for understanding how the familial space becomes the site of adolescent girls' artistic labor and household elegancies.